Informative Patterns of Health-Care Utilization Prior to the Diagnosis of Pancreatic Ductal Adenocarcinoma. Issue 8 (24th May 2017) - Coté, Gregory A; Xu, Huiping; Easler, Jeffery J; Imler, Timothy D; Teal, Evgenia; Sherman, Stuart; Korc, Murray
Abstract: Early-detection tests for pancreatic ductal adenocarcinoma (PDAC) are needed. Since a hypothetical screening test would be applied during antecedent clinical encounters, we sought to define the variability in health-care utilization leading up to PDAC diagnosis. This was a retrospective cohort study that included patients diagnosed with PDAC in the Indianapolis, Indiana, area between 1999 and 2013 with at least 1 health-care encounter during the antecedent 36-month period ( n = 1, 023). Patients were classified by unique patterns of health-care utilization using a group-based trajectory model. The prevalences of PDAC signals, such as diabetes mellitus (DM) and chronic pancreatitis, were compared. Four distinct trajectories were identified, the most common (42.0%) being having few clinical encounters more than 6 months prior to PDAC diagnosis (late acceleration). In all cases, a minority of persons had DM (30.6%, with 9.5% <1.5 years before PDAC) or any pancreatic disorder (39.9%); these were least common in the late-acceleration group (DM, 14.7%; any pancreatic disorder, 32.1% ( P < 0.001)). The most common pattern of antecedent care was having few clinical encounters until shortly before PDAC diagnosis. Since the majority of patients diagnosed with PDAC do not have an antecedent PDAC signal, early-detection strategies limited to these groups may not apply to the majority of cases.